Event-related magnetic fields in the auditory cortex of man during unilateral movements: a discriminant function analysis - Nikouline, Vadim V; Ilmoniemi, Risto J; Kulikov, Gennadiy A (Neuroscience letters, 1998)
It is often assumed that sensorimotor coordination is a feature of the sensorimotor areas of the neocortex only. The purpose of the present study was to examine how this phenomenon is reflected in the auditory cortex of man. Ten subjects were engaged in a stimulus–reaction paradigm, in which each of two acoustical tones was associated to either of two motor reactions. Magnetic fields recorded with a 122-channel magnetometer were modelled by current dipoles. The spatial coordinates as well as the amplitudes of the dipoles were analyzed from 90 to 110 ms after stimulus onset using discriminant analysis. The results suggest that the dipole trajectory in the auditory cortex of the right hemisphere and amplitudes of the dipoles in the auditory cortex of the left hemisphere already 90–110 ms after the beginning of the stimulus could be affected not only by physical features of the stimulus, but also by the motor task required as a reaction.